(untitled) (Politeja, 2015)
On Fundamental Meaning of Interpretation The article looks at the field of hesitant self-definitions reflecting ambiguities of scientific thinking in a rapidly changing (late) modern world. It concentrates on matters belonging to the domain of political science, bringing to light a fundamental question – how should we understand a current crisis of legitimacy undermining the canons of scientific knowledge, plunged in contradictions, stretched between two opposite poles of technical efficiency and communicative rationality. It advances the conception of a radical revision aimed at counterbalancing the influence of a positivist tradition, celebrating the idea of empirical knowledge, following the demands of a “scientific” method. In expectation to open a new and promising perspective it puts forward a conception of experience concentrating on language (language is looked upon as a spehere of primary and most important experience). In this effort the article brings to focus the questions of understanding and interpretation, putting to the fornt line the notion of heremenutics and considering possible advantages resulting from establishing links between cultural anthropology and political science.